Climate Change Scenarios for Central Iran (2030-2100) - Sadatinejad, Seyyed Javad; Soleimani Sardoo, Farshad; Mirzavand, Mohammad; Haryono, Eko (Indonesian Journal of Geography, 2025)
This study examines the impact of climate change on key climatic parameters—temperature, rainfall, and wind speed—in Iran’s central plateau, a region highly vulnerable to climate variability. Long-term data from major synoptic stations in Isfahan, Kerman, Yazd, and Semnan were analyzed using the Statistical Downscaling Model (SDSM) with the CanESM2 model. Future climate conditions were projected for the mid-century (2030–2060) and end-century (2070–2100) periods under RCP2.6, RCP4.5, and RCP8.5 scenarios. The analysis indicates a general warming trend across all stations, with changes in precipitation and wind speed that vary spatially. In the near future, some stations are expected to experience reduced rainfall and an average temperature increase of 1–2°C, while others may see slight precipitation increases. Wind speed trends also vary regionally. This study provides a comprehensive multi-variable assessment for a region with limited prior analysis, integrating projections for temperature, rainfall, and wind speed under multiple scenarios. Furthermore, this study is among the first to combine the SDSM and CanESM2 models to assess multi-variable climate change impacts in Iran’s arid central plateau. The results offer a concise summary of anticipated climate changes, without providing detailed interpretation or policy recommendations, thereby establishing a solid foundation for further research and planning.Received: 2024-10-30 Revised: 2025-09-17  Accepted: 2025-11-16 Published: 2025-11-17